Impacts of Asset Utilization, Market Competition and Market Distance on Stock Returns - Jeanne-Claire Patin; Matiur Rahman; Muhammad Mustafa (STIE Malangkucecwara, 2021)
To empirically study the effects of asset utilization, market competition and market distance on stock returns of 1961 US public firms of different industry categories over 2001-2015. The heterogeneous panel data set consists of 23,532 (N= 1961*T= 15) observations. Pedroni’s panel co-integration, panel vector errorcorrection model (PVECM), panel dynamic OLS (PDOLS), and panel generalized method of moments (PGMM) are implemented. Both asset utilization and market competition have short-run and long-run positive effects on stock returns. But the effects of market distance are negative. The evidence for convergence toward the long-run equilibrium is very weak. Firms should be strategic to improve asset utilization, be more competitive and expand market distance to maximize stockholders’ wealth.